Letter From the Editor - Gary J. Burkholder (Laureate Education Inc, 2017)
Here we are, already halfway through 2017! Both 2016 and 2017 have been years of transition for HLRC. In 2016 our acceptance rate was 52%. We published a special issue in June on global public good, coedited by two experts in that area-Dr. William Plater and Dr. Genevieve Shaker. We also became indexed by ERIC, and our indexing in the Directory of Open Access Journals (DOJ) was renewed. Registered users and readers of the website have increased, which is an indication that readership is expanding over time. This year will be no less busy. At the beginning of 2017, we moved to two compiled issues per year; however, we also began publishing upon acceptance, meaning that articles are published online as they are reviewed and accepted for publication. We are also looking forward to upgrading to Open Journal Systems (OJS) 3.0, which will bring a different look and feel to the journal. We continue to seek doctoral students and those with doctoral degrees to serve as peer reviewers. This is one of the best services that we, as researchers, give back to the discipline. It is a great way to keep on top of the kinds of research being conducted, and, as many of us have found, reviewing manuscripts helps to make us better writers. Also, consider the HLRC for your publication needs. The journal is open access, which means that your readership likely will be enhanced. The journal focuses on topics relevant to higher (tertiary) education. Please check the homepage to see the kinds of articles published in the journal, and browse the back issues as well. If you have any question about whether an article would be appropriate for HLRC, feel free to send an e-mail to hlrceditor@laureate.net.